THE ROLE OF UZBEK NATIONAL FOLK GAMES IN SPIRITUAL AND MORAL EDUCATION - Nargiza Isaqova (International Journal on Orange Technologies, 2021)
This article talks about the role of Uzbek national games in spiritual and moral education. The author describes the historical origins of the games in the article.